The Influence of User Experience, Sytem Quality, and Product Quality on Repurchase Intention with User Satisfaction as an Variabel Intervening Among Uniqlo App User - Fransiskus, Ronaldo; Lubis, Arlina Nurbaity; Fadli, Fadli (Formosa Journal of Multidisciplinary Research, 2024)
This study aims to assess and analyze how user experience, system quality, and product quality impact repurchase intention, mediated by user satisfaction, among UNIQLO app users. The population includes UNIQLO app users in Medan City, although the exact number is not specified. A sample of 220 respondents was selected, and the analysis was conducted using the SEM-PLS method. Findings reveal that both user experience and product quality have a direct, positive, and significant effect on user satisfaction and repurchase intention. System quality also has a direct, positive, and significant impact on user satisfaction, but its direct influence on repurchase intention is positive yet not significant. Indirectly, user experience, system quality, and product quality positively and significantly affect repurchase intention through user satisfaction among UNIQLO app users.